D=51/77
First set up the equation equal to zero(0), the distribute from there.
<h2><u><em>
If you rather have the link to get this info lmk!!</em></u></h2>
Example: f(x) = 2x+3 and g(x) = x2
"x" is just a placeholder. To avoid confusion let's just call it "input":
f(input) = 2(input)+3
g(input) = (input)2
Let's start:
(g º f)(x) = g(f(x))
First we apply f, then apply g to that result:
Function Composition
- (g º f)(x) = (2x+3)2
What if we reverse the order of f and g?
(f º g)(x) = f(g(x))
First we apply g, then apply f to that result:
Function Composition
- (f º g)(x) = 2x2+3
We get a different result! When we reverse the order the result is rarely the same. So be careful which function comes first.
<h2 />
Answer:
4 3/4
Step-by-step explanation:
Answer:
y = 4
Step-by-step explanation:
(2/3 + 4) + (-3/2y + 1/3y) = 0
(-3/2y + 1/3y) = -4 2/3
-9/6y + 2/6y = -14/3
-7/6y = -14/3
cross-multiply:
-21y = -84
y = 4
Answer:
y-x-1 < 0
Step-by-step explanation:
according to the graph (0,1) and (-1,0) lies on the doted line,
equation of the dotted line is y-x-1=0
shaded region = y-x-1 < 0